2017
DOI: 10.1590/0104-1428.2281
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da influência do condicionamento higrotérmico nas propriedades viscoelásticas de compósitos termoplásticos

Abstract: ResumoO contínuo crescimento na utilização de compósitos termoplásticos em componentes estruturais na indústria aeroespacial deve-se, primordialmente, à flexibilidade de projeto, excelência de suas propriedades mecânicas e baixa massa específica, aliadas aos elevados valores de resistência mecânica e rigidez e baixa incidência de corrosão. No entanto, componentes que requerem exigências estruturais, quando expostos a ambientes agressivos como elevada temperatura e umidade, podem ter suas propriedades mecânicas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…As it was shown in [29], the moisture absorption for epoxy-based composites reinforced with both glass and carbon fabrics was nearly the same, whereas for polyphenylene sulfide-based composites, replacing the reinforcers from glass to carbon fabrics resulted in the decreases in moisture absorption magnitude from 0.2 to 0.06%. Thus, it can be concluded that the combination of polysulfones as matrix polymers with continuous carbon fibers as reinforcers provides excellent resistance to the combined effect of temperature changes and moisture absorption, which was confirmed in several experimental investigations [30][31][32]. It should be noted that the melt viscosity of the most of the high performance thermoplastics is much higher, being two to three orders of magnitude higher than thermoset polymers (in the range of 10 2 -10 4 Pa•s) [33].…”
Section: Introductionmentioning
confidence: 54%
“…As it was shown in [29], the moisture absorption for epoxy-based composites reinforced with both glass and carbon fabrics was nearly the same, whereas for polyphenylene sulfide-based composites, replacing the reinforcers from glass to carbon fabrics resulted in the decreases in moisture absorption magnitude from 0.2 to 0.06%. Thus, it can be concluded that the combination of polysulfones as matrix polymers with continuous carbon fibers as reinforcers provides excellent resistance to the combined effect of temperature changes and moisture absorption, which was confirmed in several experimental investigations [30][31][32]. It should be noted that the melt viscosity of the most of the high performance thermoplastics is much higher, being two to three orders of magnitude higher than thermoset polymers (in the range of 10 2 -10 4 Pa•s) [33].…”
Section: Introductionmentioning
confidence: 54%
“…Thus, it is essential to know the diffusion coefficient since the moisture absorbed by the polymeric composites can cause significant changes in the physico-chemical characteristics of the matrix. This behavior can reduce the mechanical strength and stiffness of the material due to the plasticization effect of the matrix, making the material more ductile, leading to the weakening of the fiber/matrix interface and, consequently, detaching the fiber/matrix interface and degrading the laminate structure 24 .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Faria et al [90] evaluated the influence of hygrothermal conditioning on the viscoelastic properties of PPS/CF laminates. Plasticization of the polymer matrix is one of the most pronounced effects of moisture absorption, reducing the glass transition temperature.…”
Section: Influence Of Thermal Properties On Pps Processingmentioning
confidence: 99%